Antibiotic synergy as a strategy for combating multidrug-resistant bacteria: a review of mechanisms and clinical implications - Malki, Alaa Mohammed; Alaeq, Rana Abdulrahim; Alosaimi, Ahlam Ayidh; Ageeli, Mawaddah Mohsen; Alshehri, Ghadah Mohammed; Shati, Riyadh Othman; Almalki, Tahani Jubran; Almalki, Abdulrahman Abdulmalek; Alotaibi, Khulod Nawaf; Alsaedi, Khalid Abdullah; Alheddi, Abdulla Mubarak (International Journal Of Community Medicine And Public Health, 2023)
Multidrug-resistant bacteria (MDRB) are a global concern due to their resistance to multiple antibiotics. The rise of MDRB is attributed to factors like antibiotic misuse and horizontal gene transfer. Limited treatment options led to increased morbidity, mortality, and healthcare costs. MDRB spreads within healthcare and community settings, posing risks to vulnerable populations. Urgent efforts are needed to combat MDRB, including antibiotic synergy, which enhances therapeutic efficacy. Synergy disrupts bacterial processes, improves penetration and intracellular accumulation, and inhibits resistance mechanisms. It is crucial in treating biofilm-associated infections. Methods like checkerboard assays and time-kill assays assess synergistic effects, while high-throughput screening enables rapid identification. The rise of multidrug resistance has prompted urgent calls for concerted efforts to address this global health crisis. Antibiotic synergy broadens treatment options, allows dose reduction, and addresses biofilm infections. Careful implementation is necessary to minimize resistance and drug interactions. Successful case studies highlight the potential of antibiotic synergy against MDRB.